Deductive and Ampliative Adaptive Logics as Tools in the Study of Creativity - Meheus, Joke (Foundations of Science, 1999)
In this paper, I argue that logic has an important role to play in the methodological study of creativity. I also argue, however, that only special kinds of logic enable one to understand the reasoning involved in creative processes. I show that deductive and ampliative adaptive logics are appropriate tools in this respect.